Preparation, modification and characterization of plasma sprayed graphite/SiO2 powder and related coating. Issue 2 (1st February 2019) - Li, Wenzhi; Gao, Lihong; Liu, Yanbo; Ma, Zhuang; Wang, Fuchi; Li, Hezhang
Abstract: During the fabrication of functional high-endothermic-enthalpy graphite/SiO2 composite coating, the oxidation and vaporization of raw materials have become serious issues in hyperthermal preparation environment. In this study, these issues were addressed through densification and modification of the feedstock powder. Then, the corresponding coating was prepared by optimized plasma-spraying parameters. By investigating the modified feedstock powder and the resulting splats and coatings by X-ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy, we realized an optimized composite feedstock powder preparation process and an ideal coating structure. The compactness of the powder reached its optimum after treating at 1400 °C for 2 h. After heat treatment densification and Ni shell covering processes, the modified powder exhibited good oxidation resistance, vaporization resistance, and spreading performance during plasma spraying. Thus, a pure and dense composite coating was prepared. Positive laser resistance performance was observed during the initial laser ablation test, which proved that this modified graphite/SiO2 coating has good application potential in the laser protection field. Moreover, this study provides an experimental basis and a feasible method for difficult-to-spray composite coatings' preparation, such as graphite/SiO2 composite.